Efficient removal of methylene blue from aqueous solutions using magnetic graphene oxide modified zeolite - Huang, Tiantian; Yan, Ming; He, Kai; Huang, Zhenzhen; Zeng, Guangming; Chen, Anwei; Peng, Min; Li, Hui; Yuan, Lei; Chen, Guiqiu (Journal of colloid and interface science, 2019)
[Display omitted] In this study, magnetic graphene oxide modified zeolite (Cu-Z-GO-M) composites with two different ratios of GO to zeolite (named Cu-Z-GO-M 1:2 and Cu-Z-GO-M 1:1) were synthesized by solid-state dispersion (SSD) method. The properties of zeolite-based composites were characterized by SEM, XRD, FTIR, XPS, and magnetization curves. In order to understand the pollutant removal performance of the as-prepared composites, methylene blue (MB) was used as the target pollutant in adsorption experiments. The removal efficiency of MB onto Cu-Z-GO-M composite was enhanced obviously with pH > 9. The adsorption capacities of MB onto Cu-Z-GO-M 1:1 were 82.147, 89.315, 97.346 mg/g at 298, 308, and 318 K, respectively. The removal ability of MB increased with the increase of GO content in modified composites. The adsorption behavior can be well described using a pseudo-second-order kinetic and Freundlich isotherm model. The thermodynamic analysis indicated the MB adsorption by Cu-Z-GO-M was a spontaneous and endothermic reaction. The results showed that the prepared Cu-Z-GO-M composite could be a promising adsorbent with good adsorption capacity and reusability for MB removal from wastewater.